Specific types of sports and exercise group participation and socio-psychological health in older people. Issue 4 (16th February 2020) - Tsuji, Taishi; Kanamori, Satoru; Saito, Masashige; Watanabe, Ryota; Miyaguni, Yasuhiro; Kondo, Katsunori
ABSTRACT: Older people who engage in sports and exercise in a group render greater benefits for socio-psychological aspects compared to exercising alone. The aim of this study was to identify the prevalence of specific types of sports and exercise groups and the association with self-rated health, depressive symptoms, and frequency of laughter among community-dwelling older people. We used cross-sectional data from the 2016 Japan Gerontological Evaluation Study and analysed 63, 465 males and 68, 497 females aged ≥65 years. The top three most popular types among males were golf (11.3%), walking (8.4%), and ground golf (6.3%). Among females, the top three were fitness exercises (13.8%), walking (8.3%), and weight exercises (6.2%). After adjusting for potential confounders, engaging in golf with a group was significantly related with excellent self-rated health (prevalence ratio, PR, 1.31 in male and 1.78 in female), low depressive symptoms (PR, 0.70 and 0.71), and a high frequency of laughter (PR, 1.12 and 1.13). Among females, walking displayed a significant relationship with all three characteristics (PR, 1.23, 0.79, and 1.06, respectively). Golf in older males and walking in older females might be the first choice for an effective programme to spread sports and exercise groups within the older Japanese community.